Predictors of Lassa fever diagnosis in suspected cases reporting to health facilities in Nigeria - Chinwe Lucia Ochu; Lorretta Ntoimo; Ikenna Onoh; Friday Okonofua; Martin Meremikwu; Sandra Mba; Akanimo Iniobong; Obinna Nwafor; Mahmood Dalhat; Cornelius Ohonsi; Chinedu Arinze; Ekpereonne Esu; et al. (Scientific Reports, 2023)
Abstract Lassa fever (LF) remains endemic in Nigeria with the country reporting the highest incidence and mortality globally. Recent national data suggests increasing incidence and expanding geographic spread. Predictors of LF case positivity in Nigeria have been sparsely studied. We thus sought to determine the sociodemographic and clinical determinants of LF positivity amongst suspected cases presenting to health facilities from 2018 to 2021. A secondary analysis of the national LF surveillance data between January 2018 and December 2021. Socio-demographic and clinical data of 20,027 suspected LF cases were analysed using frequencies and Chi-square statistics with significant p-value set at p < 0.05. The outcome variable was LF case status (positive or negative). Predictors of LF case positivity were assessed using multiple logistic regression models with 95% confidence intervals (CI). Case positivity rate (CPR) for the four years was 15.8% with higher odds of positivity among age group 40–49 years (aOR = 1.40; 95% CI 1.21–1.62), males (aOR = 1.11; 95% CI 1.03–1.20), those with formal education (aOR = 1.33; 95% CI 1.13–1.56), artisans (aOR = 1.70; 95% CI 1.28–2.27), religious leaders (aOR = 1.62; 95% CI 1.04–2.52), farmers (aOR = 1.48; 95% CI 1.21–1.81), and symptomatic individuals (aOR = 2.36; 95% CI 2.09–2.68). Being a health worker (aOR = 0.69; 95% CI 0.53–0.91), a teacher (aOR = 0.69; 95% CI 0.53–0.89) and cases reporting in the 3rd quarter (aOR = 0.79; 95% CI 0.69–0.92) had lower odds. In a sex-disaggregated analysis, female farmers had higher odds of positivity (aOR = 2.43; 95% CI 1.76–3.38; p < 0.001) than male farmers (aOR = 1.52; 95% CI 1.19–1.96; p < 0.01). Fever (aOR = 2.39; 95% CI 2.00–2.84) and gastrointestinal (GI) symptoms (aOR = 2.15; 95% CI 1.94–2.37) had the highest odds among symptoms. Combination of fever and GI symptoms (aOR = 2.15; 95% CI 1.50–3.10), fever and neurological symptoms (aOR = 6.37; 95% CI 1.49–27.16), fever and musculo-skeletal symptoms (aOR = 2.95; 95% CI 1.37–6.33), fever and cardiopulmonary symptoms (aOR = 1.81; 95% CI 1.24–2.64), and cardiopulmonary and general symptoms (aOR = 1.50; 95% CI 1.19–1.89) were also predictive. Cumulative LF CPR appears high with clearly identified predictors. Targeted interventions with heightened index of suspicion for sociodemographic categories predictive of LF in suspected cases are recommended. Ethnographic and further epidemiological studies could aid better understanding of these associations.